PERAN AYAH DALAM PROSES PERTUMBUHAN ANAK DALAM PERSPEKTIF AL-QUR’AN - Herlena, Winceh (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2021)
This article discusses the views of the Koran on the role of fathers in the process of child development. The focus of the study in this research is to explore the verses of the Qur'an related to the role of the father in the family. In addition, this article will also describe the story of the father in the Qur'an. This research is a type of library research. The method used in this research is descriptive-analysis using a classical-contemporary interpretation paradigm approach. From the analysis that has been carried out, this study concludes that: first, the Qur'an shows the role that a father should apply in the development process of his children, one of which is by monitoring and controlling children's daily lives, instilling educational values, building closeness. and good communication with children, and provide good support and direction. Second, several verses in the Qur'an describe the role of fathers who have their own way of educating their children, so that this method is relevant to be applied in the contemporary context. The father figures in question are Luqman, Prophet Ibrahim, Prophet Noah, and Prophet Ya'qub.